Statistical properties of a randomly excited granular fluid - Bray, David Jonathan (2010)
In this thesis we describe numerical simulations performed in one- and two-dimensions of a theoretical granular model called the Random Force Model. The properties of non-equilibrium steady state granular media, which this model is a simple example of, are still hotly debated.